Stock Market Performance And Modern Portfolio Theory: Case On Malaysian Stock Market And Asian Indices - Noor Azlinna, Azizan; Sorooshian, Shahryar (World Scientific and Engineering Academy and Society, 2014)
Stocks market performance measurement has long been regarded as the most interesting part in investment. Many new methods emerge every year but most of these are rooted from Modern Portfolio theory by Harry Markowitz. In this research paper, we have used the efficient frontier from modern portfolio theory to determine the best stocks performance in KLCI index from 2006-2010. The data is compared to Sharpe performance measurement and we’ve discussed on how the best performers under efficient frontier do not agree with the result of best performers under Sharpe performance measurement. We have extended our study to look into Asian Indices include Japan, India and Hong Kong while setting the US market as our benchmark by using risk and return, together with coefficient of variance to rank the indices. We have also argued on the highest risky index. To complete the study, we’ve also used Johansen co-integration test to envisage the Asian indices market direction and economy influence. We have also discovered that most of the Asia markets co-integrate and follow Japanese market (N225) rather than the US market (S&P500).